2005
DOI: 10.1128/jcm.43.10.5136-5142.2005
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Burkholderia cepacia Complex: Evidence for New Epidemic Clones Infecting Cystic Fibrosis Patients in Italy

Abstract: To analyze national prevalence, genomovar distribution, and epidemiology of the Burkholderia cepacia complex in Italy, 225 putative B. cepacia complex isolates were obtained from 225 cystic fibrosis (CF) patients attending 18 CF centers. The genomovar status of these isolates was determined by a polyphasic approach, which included whole-cell protein electrophoresis and recA restriction fragment length polymorphism (RFLP) analysis. Two approaches were used to genotype B. cepacia complex isolates: BOX-PCR finger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 62 publications
2
42
1
1
Order By: Relevance
“…Strain PHDC has been recovered from agricultural soil in the United States, including onion fields, and from people with CF in diverse locations in the United States and Europe, suggesting that this strain is widely distributed in the natural environment, which serves as a source of ongoing acquisition. 161,[298][299][300] Strains identical to those found in people with CF have also been isolated from onions and onion rot. 301,302 Furthermore, MLST analysis demonstrated that more than 20% of 381 CF isolates of Burkholderia were indistinguishable from strains recovered from the natural environment.…”
Section: Iiid1 Nonhealthcare Sources: Soil Organic Matter and Watermentioning
confidence: 99%
See 3 more Smart Citations
“…Strain PHDC has been recovered from agricultural soil in the United States, including onion fields, and from people with CF in diverse locations in the United States and Europe, suggesting that this strain is widely distributed in the natural environment, which serves as a source of ongoing acquisition. 161,[298][299][300] Strains identical to those found in people with CF have also been isolated from onions and onion rot. 301,302 Furthermore, MLST analysis demonstrated that more than 20% of 381 CF isolates of Burkholderia were indistinguishable from strains recovered from the natural environment.…”
Section: Iiid1 Nonhealthcare Sources: Soil Organic Matter and Watermentioning
confidence: 99%
“…Shared strains from other species in the B. cepacia complex have been reported and generally involved smaller numbers of patients. 133,161,163,164 A notable exception is B. dolosa strain SLC6, which was identified in an outbreak in a US CF center and associated with deterioration in lung function and increased mortality. 25,133 The Glasgow strain of B. multivorans was identified in an outbreak among people with CF in the city in the early 1990s.…”
Section: Iiia Person-to-person Transmission Among People With Cfmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, B. cenocepacia predominates, followed by Burkholderia multivorans (2,4,5,31,33,44). However, the species B. cepacia, found infrequently in CF patients worldwide, has an exceptionally high representation among the BCC isolates in Portugal, accounting for one-half of the number of the isolates retrieved from 1995 to 2006 (12).…”
mentioning
confidence: 99%